Dielectric properties for strontium barium titanate thin films with different thickness. (11th June 2018) - Bi, Jingjing; Shan, Lianwei; Wu, Ze; Fu, Xinghua; Hou, Wenping
ABSTRACT: In this work, Sr0.5 Ba0.5 TiO3 (SBT) thin films with different thickness were prepared on a Pt/SiO2 /Si substrate by sol-gel process. The microstructures of SBT thin films were examined by X-ray diffraction(XRD) and trans- mission electron microscopy (TEM). Morphologies of samples were characterized by field-emission scanning electron microscopy (FE-SEM) and atomic force microscopy (AFM). The influences of thickness on the microstructure and dielectric properties of SBT thin films were also studied. It is found that tetragonal perovskite crystal grains existed in SBT thin films. The results indicated that the optimum thickness is 450 nm for SBT thin films.